The Effect of Clay Addition on the Mechanical Strength of Unsaturated Polyester Hybrid Composite Reinforced with Woven Agel Leaf Fiber/Glass Fiber - Orisanto Darma Setiawan; Kusmono Kusmono; Jamasri Jamasri (Journal of Material Processing and Characterization, 2020)
In the field of material technology, natural fiber materials are candidates for reinforcement in the production of lightweight, high-strength, environment-friendly, economical composites. Hybrid composites are comprised of a variety of reinforcement, fillers, and polymers. The objective of this research was to figure out the effect of clay addition on the mechanical properties of hybrid composites reinforced with woven agel leaf fiber/glass fiber. The materials used included woven agel leaf fiber, glass fiber, clay, Yukalac BQTN 157 type unsaturated polyester resin, and methyl-ethyl ketone peroxide catalyst. Firstly, the woven agel leaf fiber was given an alkaline treatment by submersion in a 4% NaOH solution for 1 hour, then rinsed with clean water and dried in the open air for 48 hours. The composite manufacture process employed 3 sheets of woven agel leaf fiber and 4 sheets of glass fiber sized 25 cm × 20 cm with unsaturated polyester matrix. The manufacture method used was the vacuum bagging method with a suction pressure of –70 cmHg. The mechanical tests carried out consisted of tensile test (based on the ASTM D638 standard), bending test (based on the ASTM D790 standard), and impact test (based on the ASTM D5942 standard). The results show that an addition of 1 wt% clay was able to increase the tensile strength, bending strength, and impact strength of the hybrid composite reinforced with woven agel leaf fiber/glass fiber by 7.26%, 30.85%, and 36.25%, respectively.